INDIAN ART COMMUNICATES TO THE VIEWER THROUGH COLOR AND BEAUTY: वर्ण-सौन्दर्य द्वारा दर्शक से संवाद करती भारतीय कला - Rani, Archana (International Journal of Research -GRANTHAALAYAH, 2014)
Art and beauty - these two words are very similar in the world of art, but also very detailed. We are not able to make any difference between art and beauty on a grand scale. Beauty is a mental state and it is limited since time immemorial. This beautiful tree has two branches - one is nature and the other art. Artistic beauty can be considered from two angles. The first point of view is that in which we consider the artist in the center, that is, how an artwork takes shape in the imagination of the artist and how it appears in front of the audience. In the second view, the viewer is kept in the center, that is, how the artwork reacts to the mind of the viewer and how it changes in its personality or social life. Varna has special significance in the taste of any work. In fact, there is a series of light in the varna space, that is, the quality of light. The human life rhythm and time is created by 1 varna. The beautiful scheme of the varnas gives a beautiful look to the work. Varna is also described as an important part of art in the six parts of Indian art. Ancient texts such as 'Shilparatna', 'Kadambari', 'Natyashastra' and 'Vishnudharmottara Purana' are detailed descriptions of the types and importance of varnas. The source of the varna is the sun. Just as the Sun is the source of all energy, similarly the characters are also produced by its light. In the month of Magha or the rainbow which appears in the sky in the rainy season, there are seven characters in it, which causes the viewer to get sunlight 3, so the origin of the varna is the source of sunlight. The aura of different colors that we see in our daily life is possible only through light. Colors have no existence in a closed dark room, because darkness is blind. कला और सौन्दर्य-ये दो शब्द कला जगत में एक जैसे होते हुए भी बहुत विस्तृत हैं। स्थूल तैार पर हम कला और सौन्दर्य में कोई अन्तर नहीं कर पाते। सौन्दर्य एक मानसिक अवस्था है और वह देश-काल से मर्यादित है। इस सौन्दर्य रूपी वृक्ष की दो शाखायें हैं-एक प्रकृति तथा दूसरी कला। कलागत सौन्दर्य पर दो दृष्टियों से विचार किया जा सकता है। पहली दृष्टि यह है जिसमें हम कलाकार को केन्द्र में रखकर विचार करते हैं अर्थात् कलाकार की कल्पना में किस प्रकार कोई कलाकृति आकार ग्रहण करती है और वह किस रूप में दर्शकों के सम्मुख प्रकट होती है। दूसरी दृष्टि में दर्शक को केन्द्र में रखा जाता है, अर्थात् कलाकृति को निरख दर्शक के मन में क्या प्रतिक्रिया उत्पन्न होती है और उसके व्यक्तित्व अथवा सामाजिक जीवन में किस प्रकार कितनी मात्रा में परिवर्तन करती है। किसी भी कृति के रसास्वादन में वर्ण का विशेष महत्व है। वस्तुतः वर्ण स्पेस में प्रकाश की शृंखला है, अर्थात् प्रकाश का गुण है।1 वर्णों द्वारा ही मानव-जीवन लय तथा रसमय होता है। वर्णों का सुन्दर योजन ही कृति को मनोरम रूप प्रदान करता है। भारतीय कला के छः अंगों में वर्ण भी कला के महत्वपूर्ण अंग के रूप में वर्णित है। ‘शिल्परत्न’, ‘कादम्बरी’, ‘नाट्यशास्त्र’ तथा ‘विष्णुधर्मोत्तर पुराण’ आदि प्राचीन ग्रन्थों में वर्णों के प्रकार एवं महत्व का सविस्तार वर्णन है। वर्ण का स्रोत सूर्य है। जिस प्रकार सूर्य सभी ऊर्जाओं का स्रोत है उसी प्रकार वर्ण भी उसके प्रकाश से ही उत्पन्न होते हैं।2 माघ मास में या वर्षा ऋतु में आकाश में जो इन्द्रधनुष दिखाई देता है, उसमें सात वर्ण होते हैं जो वर्ण दर्शक को सूर्य के प्रकाश के कारण ही दिखाई देते हैं।3 अतः वर्ण का उत्पत्ति-स्रोत सूर्य का प्रकाश ही है। हमें भी अपने दैनिक जीवन में विभिन्न रंगों की जो आभा दिखाई देती है, उसका अस्तित्व प्रकाश द्वारा ही संभव है। एक बंद अंधेरे कमरे में रंगों का कोई अस्तित्व नहीं होता, क्योंकि अंधेरा अंधा होता है।